Alternation of Negative Feelings According to the Non-Prototypical Scenario in the Sphere of Christian Ethics - Kominek, Andrzej (Respectus Philologicus, 2006)
Cognitive linguistics employs the terms of image schemas or some recurrent procedures of thinking related to the movements of the human body, manipulation of things or perceptional interactions. in a specific situation, the image schema enables certain cognitive procedures; it can be considered as an instruction: "How should I conceive the world in which I live and how should I behave in it?" It is difficult to define properly the number of such schemas (perhaps more than ten). The most recurrent schemas are as follows: CONTAINER, SOURCE -PATH-GOAL, BALANCE, FORCES, CENTRE - PERIPHERY, etc. This article focuses on two of them - CONTAINER and SOURCE - PATH - GOAL attempting to reveal how negative feelings affect (hatred, anger, fury, vengeance) alter. The so-called prototypical scenario of feeling alternation, which implies the destruction of the container, is described in cognitive literature. The article aims at another scenario, which is realised in the sphere of Christian ethics as an alternation of controlled negative feelings-affects.